Investigation by IR Spectroscopy and Quantum Chemical Methods 2-(4,6-Dioxo-1,3,5-Triazinan-2-Ylidene) Hydrazinecarboxyamide - Bakhtiyor, Ganiyev; Ferangiz, Aslonova (International Journal on Orange Technologies, 2023)
This article describes the synthesis and IR spectroscopy of 2-(4,6-dioxo-1,3,5-triazinane-2-ylidene)hydrazine carboxamide. The synthesized compound was investigated using the methods of elemental analysis and quantum chemical calculations performed in the ChemCraft 1.8 and Gaussian programs. The semicarbazone of isocyanuric acid was studied using IR spectroscopy methods and quantum chemical parameters compared with the theoretical data on experimental parameters using the Avogadro, ChemCraft 1.8. and Gaussian programs.